Significance of Road Infrastructure on Economic Sustainability - Ben, Sidiq Okwudili (American International Journal of Multidisciplinary Scientific Research, 2019)
This study buttressed on the theories explaining the significance of road infrastructure on economic sustainability. Road infrastructure is essential for banishing hunger, alleviating poverty, and improving the quality of human life. Road transport is a means of transport that offers door-to-door transport which is suitable for the delivery of finished goods to consumers. Road infrastructure has the potentials of transforming subsistence farming into a commercial and dynamic farming system which unlock the potentials embedded in rural areas. Understanding the conditions in which more or new road infrastructure does indeed foster economic growth is crucial for efficient management of road infrastructural project. Neoclassical growth theory, endogenous growth theory, growth pole, and growth centre theory were discussed. This paper concludes that public investment should not be constrained by accounting methods that impede a focus on economic returns, and road pricing strategy should be adopted in Nigeria because of its benefits of spreading demand for road transport, minimizing congestion and overcrowding, improving reliability and delivering benefits to the wider economy.